(untitled) (African Journal of Biomedical Research, 2024)
Sexually transmitted infections and HIV are health issues of concern and the issue of STI and HIV is public interest to university students, staff and government. The aim of the study was to determine the knowledge, attitudes and practices amongst first year students at a university setting in South Africa. A quantitative cross-sectional descriptive survey was conducted at a University of Technology in Vanderbijlpark, Gauteng Province, South Africa. A total of 362 students participated in the study resulting in a response rate of 97%. Data were collected by using an anonymous self-administered questionnaire that was adapted from validated questionnaire. Descriptive and inferential statistics were employed for data analysis using Strata mini version 13.0. The significant level of p value was determined at p<0.05. The mean age of respondents was 20.19. Generally, 92% of the students showed a sound level of knowledge about STI and HIV health-related matters and 95% displayed positive attitudes. The majority (84.3%) of students started engaging in sexual behaviour between the ages of 15-19. It is worth noting that 15.7% had never engaged in sexual activity. The majority (78.7%) of the respondents used condoms as the preferred method of prevention while 60% of the respondents were engaged in risky behaviour. First year students of a specific university in this study have high knowledge about STI and HIV health matters, however, some gaps were identified that need to be addressed